Hierarchical porosity in additively manufactured bioengineering scaffolds: Fabrication & characterisation. (October 2020) - Shalchy, Faezeh; Lovell, Christopher; Bhaskar, Atul
Abstract: Biomedical scaffolds with a high degree of porosity are known to facilitate the growth of healthy functioning tissues. In this study, scaffolds with hierarchical porosity are manufactured and their mechanical and thermal properties are characterised. Multi-scale porosity is achieved in scaffolds fabricated by Fused Deposition Modelling (FDM) in a novel way. Random intrinsic porosity at micron length scale obtained from particulate leaching is combined with the structured extrinsic porosity at millimeter length scales afforded by controlling the spacing between the struts. Polylactic acid (PLA) is blended with Polyvinyl alcohol (PVA) and an inorganic sacrificial phase, sodium chloride (NaCl), to produce pores at length scales of up to two orders of magnitude smaller than the inter-filament voids within 3D printed lattices. The specific elastic modulus and specific strength are maximised by optimising the polymer blends. The porosity level and pore size distribution of the foamy filaments within lattices are quantified statistically. Compression tests are performed on the porous samples and the observed mechanical response is attributed to the microstructure and density. Simple cellular solid models that possess power law are used to explain the measured trends and the dependence is associated with various mechanisms of elastic deformation of the cell walls. The relationship between pore architecture, pore connectivity, the blend material composition, and mechanical response of produced foams is brought out. Foams obtained using the PLA:PVA:NaCl 42%-18%–40% material blends show relatively high specific elastic modulus, specific strength and strain at failure. A quadratic power law relating the Young's modulus with the relative density is experimentally obtained, which is consistent with theoretical models for open-cell foams. 3D printing with blends, followed by leaching, produces structures with cumulative intrinsic and extrinsic porosity as high as 80%, in addition to good mechanical integrity. Graphical abstract: Image 1 Highlights: Highly porous interconnected polymeric scaffolds are prepared and characterised. Multi-scale porosity is obtained by combining lattice spacing & intrinsic porosity. Hot-mixed polymeric & particulate inorganic porogens produce open cell structures. Stiffness & strength are characterised for the obtained porous materials. Modulus & strength vs porosity is a power law, as per cellular solid theories.